A COMPARATIVE ANALYSIS OF DISPUTE RESOLUTION DYNAMICS IN ASIA - Pawel Voronin (Сравнительная политика)
China’s rise to prominence in the international community following the end of the Cold War, the growth in economic power and population numbers project that China will become the leading world power within several decades, regardless of the course its government takes. The article aimes to contribute to answering the question whether this rise will be peaceful through a comparative analysis of resolved and unresolved territorial disputes between China and groups of neighbouring states between 1986 and 2013. While previous studies have focused rather exclusively on Chinese behaviour, this text will examine both sides of the dispute and the behavior of the parties in light of regional dynamics.